Nubuat Tentang Mesias Menurut Nabi Yesaya, Yeremia, Dan Yehezkiel - Sinonim Lase; Moses Wibowo (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
Prophecies about the coming of the Messiah are recorded in the Old Testament and have been fulfilled in the New Testament. The prophecy delivered by the prophets Isaiah, Jeremiah, and Ezekiel is a prophecy of the coming of the Messiah to redeem mankind from sin and He will come as King for all nations. The arrival of the Messiah in the Old Testament is associated with the fall of the Kingdom of David and He comes as a liberator in suffering and He comes as a strengthener of the Kingdom of David. The Messiah came as a leader who brought His people into prosperity and peace. In the New Testament the Messiah came as a bringer of salvation for mankind. He came to free humans from sin and humans live in peace.